(untitled) (BIRDEM Medical Journal, 2020)
Background: Anemia and mineral bone disorders (MBD) accompany chronic kidney disease (CKD) and worsen as CKD progresses. Different biochemical parameters of CKD-MBD have been associated with anemia of CKD but are less well evaluated in low resource settings. In this study, we evaluated the role CKD-MBD disorders as a cause of anemia in CKD non-dialysis patients. Methods: This cross-sectional study recruited 115 patients with CKD who attended outpatient department (OPD) of Nephrology in BIRDEM General Hospital between January and June 2019. Patients, who were on iron, erythropoietin, calcium or vitamin D therapy in any form within the preceding 3 months and patients with known parathyroid disorders, metabolic bone diseases or anemia with definite etiology were excluded. Each patient’s demographic, clinical and biochemical parameters were recorded. Associations between anemia and serum levels of calcium (corrected), phosphate, parathyroid hormone (PTH), 25-hydroxy vitamin D [25(OH)D] and alkaline phosphatase were evaluated. Results: Total patients were 115 including 71 (61.7%) females. Mean age was 57.8 years. Most patients were in CKD stage 4 (43, 37.4%) and 5 (45, 39.1%). Mean duration of diabetes and hypertension were 12.7 and 7.2 years respectively. Mean serum creatinine (mg/dL), hemoglobin (gm/dL), calcium (mg/dL), albumin (gm/L), phosphate (mg/dL), alkaline phosphatase (U/L), PTH (pg/mL) and 25(OH)D (ng/mL) were 3.1, 10.5, 8.7, 37.9, 4.0, 119.1, 211.1 and 15.1 respectively. Hemoglobin in CKD stages 3-5 pre-dialysis patients had positive correlation with calcium and 25(OH)D and negative correlation with phosphate, alkaline phosphatase and PTH. Among these parameters of CKD-MBD, correlation with alkaline phosphatase was significant (r=-0.352, p=0.001) Conclusion: Anemia in CKD patients is multifactorial and this study concludes that CKD-MBD is yet another entity contributing to anemia in such pre-dialysis patients. Birdem Med J 2020; 10(3): 187-191